Socio-Economic Transformation of Ethnicity Based Business in Baglung, Nepal - Silwal, Sudarshan; Panta, Saroj Raj (Tribhuvan University Journal, 2025)
Ethnicity is a sociological and historical process that evolves based on economic, social, and political factors. This paper aims to analyze the socio-economic impact of ethnicity-based businesses on the local economy based on these two questions what are the socio-economic and demographic characteristics of caste-based business owners? How do ethnicity-based businesses impact social behavior and the economic outlook of Baglung? This study utilized both quantitative and qualitative method, descriptive and explanatory research design. Purposive sampling used to select 48 businesses and respondents. Face-to-face interviews were conducted as the data collection method to gather necessary information from business owners and understand the causes contributing to their operations in the current market of Baglung Bazar based on caste-based factors. This research found that most businesses catered to customers from Brahmin, Chhettri, or Magar backgrounds, with a moderate number of customers from other castes. But Dalits have the highest employment rate (41.7%) compared to other ethnic groups in the businesses. Similarly, daily customer arrival found depending on the price and quality of the products, as well as on ethnic groups, and their demands or desires and correlations found highly significant. This study concluded that there is a diverse range of investments patterns, varying levels of income depending on their investment and sale patterns, ethnicity-based business with relatively low annual profitability and lower satisfaction, particularly in government support, access to resources, and future business opportunities. This research will be beneficial for academics, researchers, and policymakers.